Artificial Intelligence in Commercial Aviation : Use Cases and Emerging Strategies - Pilon, Ricardo V. (Routledge, 2024)
"This book is a must read for aviation managers and all stakeholders that are interested in improving the business performance of airlines. In this book, the first of its kind on AI in Commercial Aviation, the author outlines how Machine Learning and AI are accelerating and improving the performance of airlines. Moreover, the author shares insights into many new use cases that emerging technology can deliver. He tackles all crucial functions from air navigation, flight operations, to sales, distribution, cargo, retailing and commercial optimization. He then looks forward to blockchain and the metaverse and its opportunities. With connected devices and the Internet of Everything (IoE), airlines can become retailers, sell, deliver and service holistic experiences tailored to individuals in real time. This requires airlines to modernize processes and practices supported by decision intelligence (AI) that ingests sophisticated insights and executes service automation in real time. Transforming airlines from a production to a services-based execution also requires departments to be aligned along overriding customer experience and profitability goals. The book demonstrates how AI can be deployed to redesign airline organization as well. The author also describes the next wave of business transformation around the integration of commercial functions using Composite AI at enterprise level. With his holistic understanding and experience in the airline industry, the author provides valuable insights and helps managers understand how to embrace ML and AI and contribute to future commercial aviation and cargo success"--